The complete mitochondrial genome of Lutjanus erythopterus (Perciformes: Lutjanidae) with phylogenetic consideration. (4th May 2017) - Zhou, Libin; Xie, Zhenzhen
Abstract: The complete mitochondrial genome of the Lutjanus erythopterus is presented in this study. The mitochondrial genome is 16, 509 bp long and consists of 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes, and a control region. The gene order and the composition of Lutjanus erythopterus mitochondrial genome were similar to that of most other vertebrates. The nucleotide compositions of the light strand in descending order are 29.74% of G, 28.14% of T, 25.95% of A, and 16.17% of C. With the exception of the NADH dehydrogenase subunit 6 (ND6) and eight tRNA genes, all other mitochondrial genes are encoded on the heavy strand. The phylogenetic analysis by maximum-likelihood (ML) method shows that the Lutjanus erythopterus was closer to Lutjanus russellii in the phylogenetic relationship.